28m
Step-by-step explanation:
Answer:
Step-by-step explanation:
If a ball bounces to a height of 5feet, the initial drop = 5feet
If the ball rebounds to 70% of its previous height after each bounce, the next height after rebouncing will be expressed as;
= 70% of 5
= 70/100 * 5
= 0.7*5
= 3.5 feet
The next height will be 0.7*3.75 = 2.45 and so on
The heights wil form a sequence as thus;
5, 3.5, 2.45...
This sequence forms a geometric progression.
To get the function that could be used to model the nth term in the sequence of heights of the ball after the initial drop, w will find the nth term of the sequence
a is the first term of the sequence
n is the number of terms
r is the common ratio
From the sequence:
a = 5
Substitute the given values into the formula
The nth tern=m required is
The function that models the nth term in the sequence of heights of the ball after the initial drop is an = 5 * 0.7(n-1)
The sequence of heights of the ball can be modeled using a geometric sequence, since the ball rebounds to 70% of its previous height after each bounce. The formula for a geometric sequence is:
an = a1 × r(n-1)
where an represents the nth term in the sequence, a1 is the initial term (in this case, the height of the first bounce), and r is the common ratio (in this case, 0.7). So, the function that could be used to model the nth term in the sequence of heights of the ball after the initial drop is:
an = 5 × 0.7(n-1)
#SPJ3
Answer:
Step-by-step explanation:
The greatest common factor of 24 and 30 is 6. The divisors of 6 are 1, 2, 3, and 6. Those are the numbers of identical necklaces that might be made from the beads. The number of beads of each color is found by dividing the total number of beads by the number of necklaces being made.
The possible numbers of necklaces are 1, 2, 3 or 6.
The numbers of (blue, green) beads on each will be (24, 30), (12, 15), (8, 10), or (4, 5), respectively.
_____
The greatest common factor (GCF) is the product of the common prime factors.
24 = 2^3×3
30 = 2×3×5
The prime factors in common are 2 and 3, so the GCF is 2×3 = 6.
y=x+2
substitution
x2 - 2x + = 4(x2-2x +1)-3
Answer:
-3x² +6x -1 = 0
Step-by-step explanation:
x2 - 2x + = 4(x2-2x +1)-3
x² - 2x = 4x²-8x +4 - 3
x²-4x²-2x+8x = 4-3
-3x² +6x = 1
-3x² +6x -1 = 0